Head and neck surgical oncology in the time of a pandemic: Subsite‐specific triage guidelines during the COVID‐19 pandemic. Issue 6 (27th May 2020) - ,; ,; Maniakas, Anastasios; Jozaghi, Yelda; Zafereo, Mark E.; Sturgis, Erich M.; Su, Shirley Y.; Gillenwater, Ann M.; Gidley, Paul W.; Lewis, Carol M.; Diaz, Eduardo; Goepfert, Ryan P.; et al.
Abstract: Background: COVID‐19 pandemic has strained human and material resources around the world. Practices in surgical oncology had to change in response to these resource limitations, triaging based on acuity, expected oncologic outcomes, availability of supportive resources, and safety of health care personnel. Methods: The MD Anderson Head and Neck Surgery Treatment Guidelines Consortium devised the following to provide guidance on triaging head and neck cancer (HNC) surgeries based on multidisciplinary consensus. HNC subsites considered included aerodigestive tract mucosa, sinonasal, salivary, endocrine, cutaneous, and ocular. Recommendations: Each subsite is presented separately with disease‐specific recommendations. Options for alternative treatment modalities are provided if surgical treatment needs to be deferred. Conclusion: These guidelines are intended to help clinicians caring for patients with HNC appropriately allocate resources during a health care crisis, such as the COVID‐19 pandemic. We continue to advocate for individual consideration of cases in a multidisciplinary fashion based on individual patient circumstances and resource availability.